Is Post‐Graduate Training Essential for Practice Readiness?. Issue 12 (20th November 2015) - Robinson, Daniel; Speedie, Marilyn
Abstract : Few things are more fundamental to the purpose of health professions training than to prepare practice‐ready health professionals. The Accreditation Council of Pharmacy Education (ACPE) Standards 2016 address graduate readiness to 1) provide direct patient care in a variety of health care settings (practice‐ready) and 2) contribute as a member of an interprofessional collaborative patient care team (team‐ready). ACPE Standards 2007 states that graduates should be prepared to deliver direct patient care. This includes the ability to design, implement, monitor, evaluate, and adjust pharmacy care plans that are patient specific and to function effectively as a member of an interprofessional team. Yet, controversy remains within the profession regarding the practice‐readiness of PharmD graduates, which has been further fueled by the recent ACCP White Paper on Collaborative Drug Therapy Management and Comprehensive Medication Management ‐ 2015. This commentary makes the case that PharmD graduates are practice‐ready and it offers a solution that may settle this lingering controversy.